Electron-Phonon Coupling and Superconductivity in RC2 (R=Y, La). (2016) - Sharma, Ramesh; Sharma, Yamini
Abstract: The electronic structure and transport properties of low temperature superconductors RC2 (Y, La) are calculated in the frame work of density functional theory. The intersection of bands at EF in the Γ-H and N-G directions gives rise to complicated Fermi surface topology and the density of states contains hybridized 4d/ 5d -orbitals of Y/ La and 2p-orbitals of C. From the low temperature specific heat, the electron-phonon coupling constant λel-ph < 1, this indicates that YC2 and LaC2 are intermediate superconductors. The superconducting critical temperature Tc is found to be 5.81 K for YC2 and 4.44 K for LaC2 .